Feasibility of Using Conservation Education Learning Devices for Class X High School Students - Puja Indryani; Ruqiah Ganda Putri Panjaitan*; Afandi Afandi (Universitas Syiah Kuala, 2023)
The curriculum in Indonesia has not yet implemented the conservation education model in learning, so there are no learning tools with the conservation education model in Indonesian schools, therefore it is necessary to carry out research regarding the preparation of conservation learning tools. This study aims to determine the feasibility of learning tools for conservation education in class X SMA. The research method used is RD using the ADDIE model which is limited to the development stage (analysis, design, development). The learning tools developed consisted of lesson plans, worksheets, power points, modules, and evaluation questions, then their feasibility was tested by being validated by five validators and analyzed using Aiken'S V to determine validity and ICC (Intraclass Correlation Coefficient) was used to determine reliability. The research instrument used was a validation sheet. The results showed that the validity value of the lesson plan was 0.89, the validity value of the worksheet was 0.86, the power point validity value was 0.88, the module validity value was 0.88, and the evaluation item validity value was 0.88 and all were included in the category of very high content validity. The results of lesson plan reliability were 0.933, LKPD reliability values were 0.937, power point reliability values were 0.898, module reliability values were 0.973, and evaluation item reliability values were 0.939 and all included in the very good category. It can be concluded that the conservation education learning tools for class X SMA are appropriate to use.